A detailed study on the reflection component for the black hole candidate MAXI J1836−194. Issue 2 (12th February 2020) - Dong, Yanting; García, Javier A; Liu, Zhu; Zhao, Xueshan; Zheng, Xueying; Gou, Lijun
ABSTRACT: We present a detailed spectral analysis of the black hole candidate MAXI J1836−194. The source was caught in the intermediate state during its 2011 outburst by Suzaku and RXTE . We jointly fit the X-ray data from these two missions using the relxill model to study the reflection component, and a steep inner emissivity profile indicating a compact corona as the primary source is required in order to achieve a good fit. In addition, a reflection model with a lamp-post configuration (relxilllp ), which is normally invoked to explain the steep emissivity profile, gives a worse fit and is excluded at 99 per cent confidence level compared to relxill . We also explore the effect of the ionization gradient on the emissivity profile by fitting the data with two relativistic reflection components, and it is found that the inner emissivity flattens. These results may indicate that the ionization state of the disc is not constant. All the models above require a supersolar iron abundance higher than ∼4.5. However, we find that the high-density version of reflionx can describe the same spectra even with solar iron abundance well. A moderate rotating black hole ( a * = 0.84–0.94) is consistently obtained by our models, which is in agreement with previously reported values.